Islam through Western eyes from the crusades to the war on terrorism - Lyons, Jonathan (Columbia University Press, 2012)
"In Islam Through Western Eyes, Jonathan Lyons unpacks Western habits of thinking and writing about Islam, conducting a careful analysis of the West's grand totalizing narrative across one thousand years of history. He observes the discourse's corrosive effects on the social sciences, including sociology, politics, philosophy, theology, international relations, security studies, and human rights scholarship. He follows its influence on research, speeches, political strategy, and government policy, preventing the West from responding effectively to its most significant twenty-first-century challenges: the rise of Islamic power, the emergence of religious violence, and the growing tension between established social values and multicultural rights among Muslim immigrant populations."--Jacket